The Use of Extraction Methods for Recovering Metals and Carriers from Spent Carbon Sorbents and Catalysts - E. Bezak-Mazur; L. Dąbek; M. Repelewicz; A. Świątkowski (Adsorption Science & Technology)
The usefulness of extraction methods such as leaching, extraction with complex-forming organic solvents and supercritical extraction in recovering metals and carbon carriers from dangerous wastes such as carbon impregnates and catalysts is discussed.